2007
DOI: 10.1016/j.micinf.2007.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania DNA is rapidly degraded following parasite death: an analysis by microscopy and real-time PCR

Abstract: To cite this version:Eric Prina, Emeric Roux, Denise Mattei, Geneviève Milon. Leishmania DNA is rapidly degraded following parasite death: an analysis by microscopy and real-time PCR.. Microbes and Infection, Elsevier, 2007, 9 (11) Abstract Control of human leishmaniases relies on appropriate diagnosis and reliable methods for monitoring chemotherapy. The current method used for estimation of parasite burden during chemotherapy patient follow-up as well as in pharmacological studies performed in experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 28 publications
1
87
0
3
Order By: Relevance
“…In this study, we found Leishmania DNA in all of the detected desert lizard species with exception to H42 H41 H40 H39 H38 H37 H36 H35 HG512925 H8 H4 H6 / HG 512919 H14 H3 H13 H5 H1 H2 H10 H11 HG512927 H23 H22 H21 H20 H19 H18 H17 H16 H15 H12 H7 HG512922 H9 HG512908 HG512948 T. przewalskii. Because DNA persists in the serum for approximately 24 h (Prina et al, 2007), positive results of PCR become a good indicator of current or recent infection. Our results demonstratethat the occurrence of Leishmania species varies among lizard species, with E. velox roborowskii showing lower prevalence value (56%) than do others.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found Leishmania DNA in all of the detected desert lizard species with exception to H42 H41 H40 H39 H38 H37 H36 H35 HG512925 H8 H4 H6 / HG 512919 H14 H3 H13 H5 H1 H2 H10 H11 HG512927 H23 H22 H21 H20 H19 H18 H17 H16 H15 H12 H7 HG512922 H9 HG512908 HG512948 T. przewalskii. Because DNA persists in the serum for approximately 24 h (Prina et al, 2007), positive results of PCR become a good indicator of current or recent infection. Our results demonstratethat the occurrence of Leishmania species varies among lizard species, with E. velox roborowskii showing lower prevalence value (56%) than do others.…”
Section: Discussionmentioning
confidence: 99%
“…Parasite genome integrity was assessed by the TUNEL assay (35). PIPs visualized in iNOS + cells showed no TUNEL + nuclei, but 26 ± 15% of PIPs showed TUNEL + kinetoplast (mitochondrial) DNA (Fig.…”
Section: Most Pips Are Found Within Inos + Mφs and Dcs And Show Unexpmentioning
confidence: 99%
“…The result of the present study showed comparable efficiency of the real time-PCR assay to the nested PCR, which is being used widely for the diagnosis of leishmaniasis. The existence of one (4.3 %) false-negative could have resulted from factors such as the technique employed for sample extraction, the presence of inhibitors, or the degradation of DNA, particularly kDNA, which is more readily degraded than nuclear DNA (Prina et al 2007). The kDNA nested-PCR and real-time PCR presented the same analytical sensitivity level (1 parasite/ml) and specificity.…”
Section: Discussionmentioning
confidence: 99%